Color Imaging IX: Processing, Hardcopy, and Applications 2003
DOI: 10.1117/12.529991
|View full text |Cite
|
Sign up to set email alerts
|

Gray tracking correction for TFT-LCDs

Abstract: The consistency of the white point with the input gray level is referred in the world of display technology as gray tracking [1]. Gray tracking is an issue for Twisted Nematic (TN) TFT-LCD screens which typically show a bluish color shift of the white point when the gray level decreases. This paper discusses some causes of this color shift in TN displays and proposes a method for correcting it by using the existing video card look-up tables (VLUT) in the graphic controller driving the panel. The correction pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 2 publications
0
9
0
Order By: Relevance
“…Furthermore, for some LCDs, there can be a significant lack of independence, due to inherent optical and electronic properties. More details about both assumptions can be found in Silverstein, 10 Marcu and Chen, 11 and Yoshida and Yamamoto. 12 If the assumptions of channel scalability and independence are not met, more complex approaches are required (e.g., see references 6, 12, 13, and 14).…”
Section: Introductionmentioning
confidence: 98%
“…Furthermore, for some LCDs, there can be a significant lack of independence, due to inherent optical and electronic properties. More details about both assumptions can be found in Silverstein, 10 Marcu and Chen, 11 and Yoshida and Yamamoto. 12 If the assumptions of channel scalability and independence are not met, more complex approaches are required (e.g., see references 6, 12, 13, and 14).…”
Section: Introductionmentioning
confidence: 98%
“…Consequently, it is difficult to predict accurate tone reproduction curves of LCD's only by brightness matching. To solve this problem, adjusting the brightness and hue of gray by spectrophotometer is reported 6,7 , however it is difficult to use these tools for the work of prepress, because the spectrophotometer is relatively expensive as mentioned before. For adjusting a display accurately but reasonably, we developed the method to adjust both the brightness and the hue of a continuous tone image area in Fig.2 to binary image area with human eyes.…”
Section: The Tone Reproduction Of Three Primary Colors (Red Green Amentioning
confidence: 98%
“…In addition, LCD has a characteristic that chromaticity of gray, having equal RGB values, becomes more bluish as the gray gets darker. [5][6][7] In Fig.3, chromaticities of gray on LCD and CRT are plotted. Fig.3 shows the LCD has significant hue shift but the CRT does not have.…”
Section: The Tone Reproduction Of Three Primary Colors (Red Green Amentioning
confidence: 99%
“…First, in some LCDs there are local anomalies of grayscale, with some digital steps producing no luminance change and others producing unusually large luminance changes. Second, some LCDs have problems with gray tracking, with the gray at different digital counts varying sufficiently in chromaticity to produce visible color differences (Marcu andChen, 2002, Marcu 2004). On the two high-quality LCDs used in this study, gray tracking was found to be excellent.…”
Section: The Test Batterymentioning
confidence: 99%